2019
DOI: 10.1039/c9cp03395e
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation in Janus MoSSe a monolayer and stacked bulk with vertical asymmetry

Abstract: Janus TMD materials have out-of-plane second harmonic generation behavior with their broken symmetry. It can be tuned and enhanced by patterns of stacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 45 publications
4
63
0
Order By: Relevance
“…It was also found that MoSSe has the structural phase 2H, which is reasonable in accordance with previous studies. 27,39,71 The equilibrium Mo–Se and Mo–S bond lengths are about 2.489 Å and 2.380 Å, respectively, computed by the DFT-D method reported in Table 1, and these values agree with earlier reported experiments and theory. 27,72 Weak vdW interactions between the atomic layers of the 2D MoSSe structure show a significant effect on the average bond distances between the atoms present in each layer.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It was also found that MoSSe has the structural phase 2H, which is reasonable in accordance with previous studies. 27,39,71 The equilibrium Mo–Se and Mo–S bond lengths are about 2.489 Å and 2.380 Å, respectively, computed by the DFT-D method reported in Table 1, and these values agree with earlier reported experiments and theory. 27,72 Weak vdW interactions between the atomic layers of the 2D MoSSe structure show a significant effect on the average bond distances between the atoms present in each layer.…”
Section: Resultssupporting
confidence: 89%
“…72 The lattice constants are also in accordance with the previous computed results within 0.004 A. 39 These parameters lie within the values of the lattice constants and interfacial angles of both pristine 2D monolayer MoS 2 and MoSe 2 TMDs. It was also found that MoSSe has the structural phase 2H, which is reasonable in accordance with previous studies.…”
Section: Resultssupporting
confidence: 87%
“…Polarization of the Janus materials causes dipole–dipole interactions between the polar materials or gaseous species. 42 − 44 Hence, the internal dipole interaction in the Janus materials can couple with the electronic interaction between acetone and the Janus materials and then alter the magnitude or direction of the electron transfer. In addition, based on Ohm’s law, the electric conductivity is the slope of the I – V curve, and the electron transport phenomenon before and after gas adsorption has trends similar to the results of the calculated conductivity change.…”
Section: Resultsmentioning
confidence: 99%
“…They generally exhibit a sandwich structure with the form of X-M-X (MX 2 , where M and X represent transition metal and chalcogen element, respectively), such as WS 2 and WSe 2 , whose upper and lower layers have the same element. Interestingly, a new type of TMDCs, namely Janus structure of X-M-Y (X and Y represent different chalcogen elements, respectively) [12][13][14], shows many new features owing to the particular structures, such as strong Rashba spin-orbit coupling (SOC) effect [15,16], large valley splitting [17,18], strong piezoelectric effect [19], and so on. For example, Yao et al reported that the Rashba coefficient of singlelayer WSeTe is up to 0.92 eVÅ [15], which is even higher than that in traditional semiconductor heterojunctions of InGaAs/InAlAs [20] and LaAlO 3 /SrTiO 3 [21].…”
Section: Introductionmentioning
confidence: 99%